Age, Depositional Environment, and Characteristics of Palynomorph Fossil in the Batuasih Formation, Sukabumi, West Java - Rachman, Rizki Satria; Winantris, Winantris; Muljana, Budi (Metamorfosa: Journal of Biological Sciences, 2021)
Palynomorph is a dust-sized material that is resistant to strong acids which can reflect the age and environmental conditions when a rock was formed. Batuasih Formation is one of the oldest rock formations in Bogor Basin which is rarely interpreted, especially from its palynological aspect. This study aims to see palynomorph characteristics, relative age, and environmental conditions in Batuasih Formation. There are several steps in conducting the research. Field activities by measured stratigraphic sections and sampling every 5-meter intervals or each lithological changes, laboratory activities by sample preparation using acid treatment method, identification were carried out using CX-22 binocular microscope, and laboratory analysis of age and depositional environment is drawn based on palynomorph associations that are present in rocks. The result found that palynomorphs were present in 8 of 10 samples (B.1, B.2, B.4, B.6 - B.10). One hundred seventy-three palynomorphs identified to consist of 20 different species. Dominant pollen came from genus Proxapertites, both Proxapertites operculatus, Proxapertites cursus, and Proxapertites psilatus. While dominant spores came from Verrucatosporites usmensis. Apart from pollen and spores, Palynomorphs in the form of dinoflagellates and foraminifera test lining are also present in this formation. Palynomorph analysis shows that Batuasih Formation has Late Eocene - Early Oligocene age (41.2 - 27.8 Ma) with transitional depositional environment.